Effect of aPDT on Streptococcus mutans and Candida albicans present in the dental biofilm: Systematic review - Fumes, Ana Caroline; da Silva Telles, Paloma Dias; Corona, Silmara Aparecida Milori; Borsatto, Maria Cristina (Photodiagnosis and photodynamic therapy, 2018)
To evaluate the effect of aPDT on S. mutans and C. albicans present in the dental biofilm, using methylene blue as a photosensitizer in different pre-irradiation times. The searches were made on Pubmed, Web of Science, Bireme, Scopus and Cochrane Library, and were complemented by screening the references of selected articles in the attempt to find any article that did not appear in the database search. The searches were performed by two researchers and limited to studies involving human subjects published in the English language. Inclusion criteria included in vitro studies with aPDT; studies that used methylene blue as a photosensitizer; studies that used low power laser; studies that evaluated S. mutans or C. albicans. Studies published in a non-English language, patents, in vivo or in situ studies; case reports, serial case, reviews and animal studies were not included. Studies published before 1996 were also not included. Initially, the search resulted in 68 published studies. 16 records were excluded because they were duplicated. The analysis of titles and abstracts resulted in the exclusion of 48 of the published studies, resulting in 4 studies included in the systematic review. The aPDT was effective in three of the four papers selected for the systematic review and the pre-irradiation time used was 5 or 15 min. This therapy had satisfactory results in both C. albicans and S. mutans when using methylene blue as a photosensitizer.